Community Preparedness to Reduce Risk Disaster of Tsunami - Putra Agina Widyaswara Suwaryo; Dela Gustia Rahma; Barkah Waladani; Aprilia Safaroni (Babali Nursing Research, 2021)
Introduction: Kebumen is one of the districts that has a high level of disaster vulnerability in Central Java. Most of area is lowland and village located in a coastal area and close to the beach so that it has a tsunami disaster. This research is to describe level of knowledge, attitude, disaster plan, emergency disaster, early warning system, mobilization of resources in a tsunami disaster. Methods: This study is a descriptive study with 98 respondents were all members of the community. The sampling technique used purposed sampling with 50 questionnaires, and analysis determine the proportion based on the categories of good, adequate and insufficient. Results: The level of knowledge and attitudes of the disaster community is in the bad category (51%), level of family policies is in the moderate category (52%), level of emergency response plans is in the moderate category (72.4%), and level of the warning system bad category (56.1%). Meanwhile, the level of resource mobility was in the bad category (71.4%). Conclusion: The results of community preparedness in Kebumen in the face of tsunami disaster based on 5 parameters were found that the community wasn’t ready.